Effect of exercise intervention for arthralgia in patients with knee osteoarthritis ("骨痹操"锻炼干预膝骨关节炎的临床研究) - ZHANG Sudan (张苏丹); TANG Ling (唐玲); MA Junfu (马俊福); LI Suqian (李苏茜); ZHAO Lixue (赵丽雪); YAO Jianshuang (姚建爽); WANG Huaxin (王华新) (Journal of International Translational Medicine Limited, 2021)
Objective To explore the effect of exercise intervention for arthralgia in patients with knee osteoarthritis. Methods Totally 80 patients with knee osteoarthritis recruited were selected as the research objects. Patients were divided into observation group (n=29) and control group(n=51). The control group was given oral administration of Glucosamine Sulfate, Jintiage Capsules and external application of diclofenac diethylamine emulsion. In the observation group, on the basis of the control group, the bone arthritis exercise was used for intervention. The disease awareness, Body Mass Index (BMI), Visual Analogue Scale (VAS) score, WOMAC score and clinical syndrome quantitative score of the two groups were observed and recorded. Results After 12 weeks of treatment, the cognitive function scores of 2 groups were significantly increased, and cognitive function score in observation group were higher than that in the control group (P＜0. 05). The VAS score, WOMAC score and clinical syndrome quantification score in two groups were significantly decreased, and lower outcomes of VAS, WOMAC and clinical syndrome quantification were found in the observation group compared with those in the control group(P＜0. 01). The overall effective rate in the observation group was higher than that in the control group (P＜0. 01). Conclusion The application of exercise intervention for arthralgia is potentially effective to increase patient's awareness, relieve the knee pain, improve the function of the knee joint and relieve the clinical symptoms of patients. (目的 探讨"骨痹操"锻炼在膝骨关节炎患者中的应用效果。方法 选取80例膝骨关节炎患者为研究对象, 分为观察组29例和对照组51例。对照组给予口服硫酸氨基葡萄糖和金天格胶囊、外用双氯芬酸二乙胺乳胶剂; 观察组在对照组的基础上采用"骨痹操"锻炼进行干预。观察并记录2组患者的认知度、BMI值、VAS评分、西安大略大学和麦克马斯特大学骨关节炎指数(WOMAC)评分及临床证候量化评分。结果 治疗12周后, 2组患者认知功能评分均增加, 且观察组的认知状况评分明显高于对照组(P＜0. 05)。2组患者VAS评分、WOMAC评分及临床证候量化评分均降低, 且观察组VAS评分、WOMAC评分和临床证候量化评分低于对照组, 差异有统计学意义(P＜0. 01)。观察组总有效率高于对照组, 差异有统计学意义(P＜0. 01)。结论 运用"骨痹操"锻炼对膝骨关节炎患者进行干预, 能明显提高患者认知度, 减轻患膝疼痛, 改善膝关节功能, 缓解患者临床症状。)